Taxation of Insurance - Vidar Christiansen (Center for Economic Studies and ifo Institute (CESifo), 2017)
Should we exempt the services of insurance companies from VAT? Addressing this issue, the paper distinguishes between insurance against a general loss of resources and a loss of a specific commodity (property insurance). There is a case for exempting the former kind of insurance, but not the latter. Finally, comparing insurance through a producer warranty with insurance provided separately by an insurance company, it is conceivable that tax exemption of the latter will distort the choice of product quality.
Keywords: H21; 330; insurance; warranties; value added tax; VAT exemptions